KEBIJAKAN INDONESIA DALAM MEMBANTU PENYELESAIAN KONFLIK ANTARA ETNIS ROHINGYA DAN ETNIS RAKHINE DI MYANMAR (STUDI KARAKTER KEPRIBADIAN SUSILO BAMBANG YUDHOYONO) - Ardani, Fatma Arya; Wahyudi, Fendy Eko; Susetianingsih, Hermini (Journal of International Relations, 2015)
Humanitarian issues in Myanmar, in May 2012 was an issue thatdrew international attention, including Indonesia. The ethnic conflictbetween Rohingya and Rakhine led to crime against humanity.Following the humanitarian crisis in Myanmar, Indonesia promotepeace between Rohingya and Rakhine. This study seeks to explainIndonesia’s foreign policy in the case of ethnict conflict in Myanmar.This research employed idiosyncratic approach to explain therelationship between Indonesia’s foreign policy and personalcharacters of the leader. Conciliatory character of Susilo BambangYudhoyono’s leaderships affects participatory orientation inIndonesia’s foreign policy. Susilo Bambang Yudhoyono as Indonesiapresident become an important actor in policy making to promotepeace resolution in Myanmar. Using library research, this study foundthat the conciliatory character of Susilo Bambang Yudhoyono playedan crucial factor behind the Indonesia’s foreign policy in Myanmar